Analisis Problematika Pembelajaran Jarak Jauh Pada Kurikulum 2013 Kelas IV SDN Taman Cibodas Kota Tangerang - Novfa Rizka Zahra (Nusa Putra University, 2021)
The background of long distance learning process for 2013 curriculum can be found in this research. This research inspired to identify distance learning problems in the scientific approach for Grade IV-2013 curriculum. This study uses the descriptive qualitative research, methods used for observation; interview; and documentation. The result of this research shown that the implementation of distance learning for class IV students at SDN Taman Cibodas has been going quite well. The teacher distributed assignments and materials using applications such as Google Meet, Zoom meeting, and Whatsapp groups. Regarding the plain execution of the 2013 curriculum in Class IV, the application of the scientific approach can not be carried out optimally, to be specific at the stage of asking, collecting information and associating the obstacles faced during class. It caused because the lack of communication created by students during the learning process and there must also be a face-to-face session in teaching-learning procedure because of the scientific process that is a assessed in it. The scientific approach is carried out with an interaction in viewing, observing or various ecperiences implemented based on learning so as to help students to optimize cognitive, affective and psychomotor values.